2021
DOI: 10.35479/ijretina.2021.vol004.iss002.169
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Central Retinal Thickness and Visual Outcome Post Intravitreal Ranibizumab Injection Loading Doses in Exudative Age Related Macular Degeneration

Abstract: Introduction : Age Related Macular Degeneration (AMD) stills the leading cause of blindness in developing countries for age 50 and above, increasing along higher life expectations.Anti- VEGF is the mainstay management for exudative AMD and able to reduce the central retinal thickness (CRT) and to increase the visual outcome. The aim of this study is to correlate between CRT and visual outcome in exudative AMD post intravitreal ranibizumab injection loading doses in Soetomo general academic hospital, Surabaya&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, two post hoc analyses and a cross-sectional study used CRT at baseline or certain fixed time points as predictors of VA. Unfortunately, weak or even no correlations were obtained [13‒15], which may be explained by the fact that simple CRT measurements are not informative enough. Limited but growing evidence from longitudinal studies suggested a significant link between the variability of CRT and visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two post hoc analyses and a cross-sectional study used CRT at baseline or certain fixed time points as predictors of VA. Unfortunately, weak or even no correlations were obtained [13‒15], which may be explained by the fact that simple CRT measurements are not informative enough. Limited but growing evidence from longitudinal studies suggested a significant link between the variability of CRT and visual outcomes.…”
Section: Introductionmentioning
confidence: 99%